Whiteness as a Dissonant State: Exploring One White Male Student Teacher's Experiences in Urban Contexts. (September 2019) - Behm Cross, Stephanie; Tosmur-Bayazit, Nermin; Dunn, Alyssa Hadley
Studies on student teaching continue to suggest that preservice teachers' feelings of dissonance are related to disparate views of teaching and learning between universities and schools. Drawing on interview, artifact, and observation data, the authors utilize Cognitive Dissonance and Critical Whiteness Studies to make different sense of the experiences of one White student teacher (Brett). Results indicate that Brett experienced dissonance related to fractured relationships, misaligned teaching strategies, and disengagement as he taught youth of color. Importantly, the use of Critical Whiteness Studies helped to additionally reveal the way Whiteness affected Brett's movements toward consonance—mainly through rationalization and problematic notions of perseverance. The authors suggest that Whiteness itself is a dissonant state, and argue that conversations focused on dissonance from misaligned university theory and K-12 schooling practices is dangerously incomplete. Implications for research and practice are included.